Hailstorm data from a fixed network for the evaluation of a hail modification experiment - Schleusener, Richard A., author; Marwitz, John D., author; Cox, William L., author; Colorado State University, publisher (Colorado State University. Libraries, 1964)
Hailfall data collected from a fixed network in northeastern Colorado during three seasons (1960-62) included the estimated impact energy, duration of hailfall, most common stone size, maximum stone size, and number of stones per square inch. These basic data, X, along with the transformations; ln X, √X, ∛X and 1/X were analyzed by computer methods to determine which parameters could be used in a statistical analysis of hail suppression experiment. The gamma distribution function was fitted to the hailfall data by the method of maximum likelihood. A chi-square goodness of fit test was applied to the data, and one transformation was tested using a sequential analysis technique. All parameters except impact energy and number of hailstones per square inch were eliminated from the statistical analysis because of bias, non-homogeneity, or sparsity of samples. Transformations which produced the minimum mean coefficient of variations were logarithm of impact energy (ln E) and square root of the number of stones per square inch (√(N_(1-6) ) ). It was determined that a target control analysis was not feasible for the analysis of hail suppression experiment. A period of 3 to 5 years is believed to be necessary to detect changes of 10 to 25 percent in the hail parameters. The gamma distribution function fitted only the (√(N_(1-6) ) ) data. From the results it was conclude that a sequential analysis test alone could not adequately evaluate the effectiveness of a hail modification experiment.
CER64RAS-JDM-WLC13.
April 1964.
Prepared for submission to Journal of Applied Meteorology.
Keywords: Hail -- Colorado; Hail control -- Colorado